Problems and Countermeasures about Chinese Stock Market - Tse, Tony (Transactions on Economics, Business and Management Research, 2024)
This paper takes China's stock market as the research object, and deeply analyzes the existing problems and causes of China's stock market through gathering information and data from the Internet and few websites. First of all, this paper briefly summarizes the development process of China's stock market and points out the problems that temporarily existed in the market: the unreasonable market structure, imbalance of investor structure, imperfect regulatory system, and large market volatility. On this basis, this paper puts forward targeted countermeasures and suggestions through the author’s analysis. Specifically, these countermeasures and suggestions are improving the market structure, optimizing the investor structure, improving the regulatory system, and reducing market volatility. In addition, this paper also emphasizes the importance of strengthening international cooperation and learning from international advanced experience. Through the analysis, the paper verifies the effectiveness of the proposed countermeasures and provides theoretical support and practical guidance for the reform and development of China's stock market. This study helps to improve the transparency and efficiency of China's stock market and promote the long-term stability and healthy development of the market.